Effect of elevated depressive symptoms during adolescence on health-related quality of life in young adulthood—a six-year cohort study with repeated exposure measurements - Wiehn, Jascha; Kurth, Tobias; Ravens-Sieberer, Ulrike; Prugger, Christof; Piccininni, Marco; Reiss, Franziska (Frontiers in Pediatrics, 2024)
Objectives. Depression is a major contributor of young people’s burden of disease. In this study we aim to estimate the effect of elevated depressive symptoms on physical health-related quality of life. Design. We used self-reported information from the prospective BELLA cohort study, which included adolescents selected from the general population in Germany. The baseline assessment (2003-2006) and the 1-, 2-, and 6-year follow-up waves provide the data basis. Participants. The baseline study population consisted of 1,460 adolescents between the ages of 12 and 17 who, according to their caregivers, did not suffer from depression. Variables. The primary outcome, as measured by the physical component score (PCS) of the SF-36 at a 6-year follow-up (range: 0-100), is physical health-related quality of life. The exposure of interest is depressive symptoms, as measured by the Center for Epidemiological Studies Depression Scale for Children (CES-DC) at baseline, 1-year follow-up and 2-year follow-ups (range: 0-60). We dichotomized the exposure into subthreshold (≤15) and elevated depressive symptoms (>15). For the main analyses we considered a cumulative index for elevated depressive symptoms across the three time points (range: 0-3). Considered confounders are sex, age, socioeconomic status, migrant background, social support, anxiety symptoms, physical activity, chronic diseases, and sleeping problems. Statistical methods. We used multiple imputation to account for missing values. Within each imputed dataset, we applied inverse probability weighting (IPW) to estimate the effect of the cumulative index for elevated depressive symptoms at baseline, 1- and 2-year follow-up on physical health-related quality of life at 6-year follow-up. We derived 95% confidence intervals by bootstrapping. Results. After adjusting with IPW, the effect of the cumulative index per one unit increase of elevated depressive symptoms on the physical component score was -1.71 (95% CI: -3.51 to -0.04). The adjusted effect estimates of single exposure of elevated depressive symptoms on physical health-related quality of life were -0.83 (95% CI: -3.69 to 1.87) at baseline, -2.96 (95% CI: -4.94 to -0.52) at 1-year follow-up and -1.32 (95% CI:-3.85 to 1.15) at 2-year follow-up. Conclusion. Findings suggest that elevated depressive symptoms during adolescence decrease physical health-related quality of life in young adulthood.